Dental profile of patients with Gaucher disease - Mann Jonathan; Sgan-Cohen Harold; Elstein Deborah; Fischman Stuart L; Zimran Ari (BMC, 2003)
Abstract Background This study was conducted to determine whether patients with Gaucher disease had significant dental pathology because of abnormal bone structure, pancytopenia, and coagulation abnormalities. Methods Each patient received a complete oral and periodontal examination in addition to a routine hematological evaluation. Results Gaucher patients had significantly fewer carious lesions than otherwise healthy carriers. Despite prevalence of anemia, there was no increase in gingival disease; despite the high incidence of thrombocytopenia, gingival bleeding was not noted; and despite radiological evidence of bone involvement, there was no greater incidence loss of teeth or clinical tooth mobility. Conclusions These data represent the first survey of the oral health of a large cohort of patients with Gaucher disease. It is a pilot study of a unique population and the results of the investigation are indications for further research. Based on our findings, we recommend regular oral examinations with appropriate dental treatment for patients with Gaucher disease as for other individuals. Consultation between the dentist and physician, preferably one with experience with Gaucher disease, should be considered when surgical procedures are planned.